Jewish love magic : from late antiquity to the Middle Ages - Saar, Ortal-Paz. (Magical and Religious Literature of Late Antiquity, 2017)
Jewish Love Magic: From Late Antiquity to the Middle Ages is the first monograph dedicated to the supernatural methods employed by Jews in order to generate love, grace or hate. Examining hundreds of manuscripts, often unpublished, Ortal-Paz Saar skillfully illuminates a major aspect of the Jewish magical tradition. The book explores rituals, spells and important motifs of Jewish love magic, repeatedly comparing them to the Graeco-Roman and Christian traditions. In addition to recipes and amulets in Hebrew, Aramaic and Judaeo-Arabic, primarily originating in the Cairo Genizah, also rabbinic sources and responsa are analysed, resulting in a comprehensive and fascinating picture.